Prediction of Heavy Oil Production Based on Geomechanical Analysis in Entire Lifecycle of SAGD - Dengke Li; Shaowen Zhu; Yanchao Li; Shijie Shen; Zupeng Chen; Zhanli Ren; Yuxuan Zhou; Yanfang Gao (Energy Science & Engineering)
ABSTRACT Steam‐assisted gravity drainage (SAGD) technology is an essential means of efficient development of heavy oil, super heavy oil, oil sands, and other unconventional resources in the world. Accurate prediction and evaluation of heavy oil output during SAGD production is a key step of construction optimization design and economic evaluation. The traditional prediction model of heavy oil production does not fully consider many geomechanical factors, such as rock deformation and permeability dynamic evolution. In this paper, a new mathematical model of crude oil production‐geomechanical coupling was established for three stages of the SAGD life cycle (steam chamber breakthrough stage, rising stage, and lateral dilation stage). The influence of the dynamic evolution of rock porosity and permeability on production was fully considered through the sensitivity coefficient of rock strain and permeability stress. It is found that the gap between the new model and the traditional model is larger when the strain and stress sensitivity of the reservoir body is larger. The value calculated by the conventional model is small when the reservoir dilates and large when the reservoir compresses. For Karamay heavy oil in Xinjiang, China, the steam breakout time predicted by the new model is 0.72, 1.50, 1.37, and 1.44 times the conventional model when the volumetric strain is 6%. The heavy oil production of Karamay, Xinjiang, China, Athabasca, and Cold Lake SAGD production areas in Canada was predicted. In the lateral dilation stage of the steam chamber, the predicted values of the model considering geomechanical factors were 1.44, 1.28, and 1.15 times the traditional model, respectively. This model can help field engineers obtain more accurate production of heavy oil and evaluate the significance of reservoir geomechanics in SAGD production.